IL-10 inducible CD8+ regulatory T-cells are enriched in patients with multiple myeloma and impact the generation of antigen-specific T-cells - Plaumann, Julian; Engelhardt, Melanie; Awwad, Mohamed; Raab, Marc-Steffen; Hillengaß, Jens; Halama, Niels; Neuber, Brigitte; Müller-Tidow, Carsten; Goldschmidt, Hartmut; Hundemer, Michael (Cancer immunology immunotherapy, 2018)
Tumor-mediated immunosuppression via regulatory T-cells is a key player among the various immune-escape mechanisms in multiple myeloma. We analyzed the generation, distribution, function and immunophenotype of CD8+CD28− regulatory T-cells in patients with multiple myeloma. Functionality of CD8+CD28− T-cells was assessed by immunological assays using ex vivo generated antigen-specific T-cells from patients with plasma cell dyscrasias and healthy donors. Detailed analysis of distribution, immunophenotype and cytotoxic potential of CD8+CD28− T-cells was performed by flow cytometry and ELISA.
Im Titel ist das Pluszeichen bei "CB8" hochgestellt
Gesehen am 23.04.2020